2020
DOI: 10.1177/0194599820970943
|View full text |Cite
|
Sign up to set email alerts
|

Does Ibuprofen Increase Bleed Risk for Pediatric Tonsillectomy?

Abstract: Objective To evaluate risk factors for pediatric posttonsillectomy hemorrhage (PTH) and the need for transfusion using a national database. Study Design Retrospective cohort study. Setting The study was conducted using the Pediatric Health Information System (PHIS) database. Methods Children ≤18 years who underwent tonsillectomy with or without adenoidectomy (T±A) between 2004 and 2015 were included. We evaluated the risk of PTH requiring cauterization according to patient demographics, comorbidities, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…Most investigations have used similar definitions of tonsil bleeding (ie, return visits) and have included both single-institution data and large databases. A previous PHIS study found a bleeding rate of 1.58%; however, it did not create a probability model, which we have shown can be useful for providing an important perspective to surgeons when self-monitoring their rates.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigations have used similar definitions of tonsil bleeding (ie, return visits) and have included both single-institution data and large databases. A previous PHIS study found a bleeding rate of 1.58%; however, it did not create a probability model, which we have shown can be useful for providing an important perspective to surgeons when self-monitoring their rates.…”
Section: Discussionmentioning
confidence: 99%
“…Leung and colleagues (2020) found that after the publication of the AAO–HNS guideline in 2011, physicians decreased opioid prescriptions, increased ibuprofen use, and that rates of PTH overall increased between 2011 and 2015 7 . Although the authors identify ibuprofen as a main risk factor, they acknowledge that their methodology did not allow them to examine ibuprofen dose, yet the findings were compelling enough for those authors to switch to 5 mg/kg/dose in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective cohort study utilizing the Pediatric Health System database (PHIS) by Leung and colleagues (2020) found an increase in PTH between 2011-2015 as compared to previous years, citing ibuprofen standardization as a possible main contributing factor. 7 A 2012 update to the original 2005 Cochrane Review included studies where a variety of nonsteroidal antiinflammatory drugs (NSAIDs) were administered, including ketorolac and variable ibuprofen dosages; this review concludes that insufficient evidence exists to rule out an increased risk of bleeding when NSAIDs are used in pediatric tonsillectomy. 8 In 2013, the FDA placed a boxed warning for codeine in children after tonsillectomy and/or adenoidectomy following a cluster of deaths attributed to the analgesic.…”
Section: Introductionmentioning
confidence: 99%
“…Over 600,000 tonsil-related treatments are reportedly carried out annually across the globe ( 1 ). However, postoperative complications remain the greatest challenge for patient recovery, occurring in about 5%–15% of cases, the most common of which is related to post-tonsillectomy hemorrhage (PTH) ( 1 , 2 ). The incidence of PTH is approximately 1%–19%.…”
Section: Introductionmentioning
confidence: 99%